Experimental co-design of jewelry from Makalani nut: The case of contemporary techniques and indigenous craft in Namibia. Issue 5 (19th October 2020) - Van Wyk, Michelle; Thurner, Thomas
ABSTRACT: This paper studies creative possibilities of co-designing with the Makalani nut when crafting and jewelry manufacturing techniques meet. The study reflects on how the artisan craft of carving, based on a rich indigenous knowledge, and previously not yet included in the field of fine jewelry, could create new artifacts that could support selfemployment and income generation to the crafting indigenous communities of Namibia. The co-design experiments served as both methodological approach and method in this paper. Sessions proved a great core foundation for collaboration and created opportunity for documentation of both process and outcomes, while also highlighting tension points linked to the industrialization of these creative processes. The concern of the inevitable impacton the social fabric of the communities beckoned the question of how indigenous knowledge is impacted when it interacts with other knowledge systems – a question this paper aims to speak to.